2016
DOI: 10.1158/1078-0432.ccr-16-1031
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Chemotherapy-Resistant Polymerase ϵ (POLE) Ultra-Mutated and MSH6 Hyper-Mutated Endometrial Tumors with Nivolumab

Abstract: Purpose The management of endometrial carcinoma no longer amenable to treatment with surgery or radiation has not improved significantly with modern chemotherapy. Alternative therapeutic options are desperately needed. Experimental Design We describe 2 heavily pretreated patients with recurrent disease refractory to surgery, radiation and chemotherapy treated with the anti-PD1 immune check-point inhibitor nivolumab. Results Patient # 1 harbored an ultra-mutated (Mutation Load/MB = 117.3, total mutations = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 9 publications
2
88
0
1
Order By: Relevance
“…A significantly better survival has also been noted for POLE -mutant CRC [44]. Recent studies suggest this could be due to the high immunogenicity of the tumors [31,34,38,41,89,90], which likely results from the hypermutation increasing the number of neoepitopes that can be recognized by the immune system [37,4042,44,92,93]. The improved survival suggests that, while the hypermutated POLE tumors are often of higher grade, they should be classified separately and could be treated less aggressively [36,94].…”
Section: Therapeutic Implications Of Dna Polymerase Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly better survival has also been noted for POLE -mutant CRC [44]. Recent studies suggest this could be due to the high immunogenicity of the tumors [31,34,38,41,89,90], which likely results from the hypermutation increasing the number of neoepitopes that can be recognized by the immune system [37,4042,44,92,93]. The improved survival suggests that, while the hypermutated POLE tumors are often of higher grade, they should be classified separately and could be treated less aggressively [36,94].…”
Section: Therapeutic Implications Of Dna Polymerase Deficiencymentioning
confidence: 99%
“…Other hypermutated tumors such as melanomas and lung cancers are also highly immunogenic [95,96]. Consequently, hypermutated tumors, including rare relapses of POLE -mutant EC, have responded well to immunotherapy [42,93,9597]. While further studies are needed, this may indicate that immunotherapy alone, if necessary, could replace radiation and chemotherapy after surgery in these cases.…”
Section: Therapeutic Implications Of Dna Polymerase Deficiencymentioning
confidence: 99%
“…Second, understanding early drivers of hypermutation may be useful for predicting the cancer's evolutionary trajectory and accumulation of additional mutations. Finally, hypermutation is correlated with response to immune checkpoint inhibitors, which can lead to durable remissions in some patients (Bouffet et al, 2016; Johanns et al, 2016; Le et al, 2015; Rizvi et al, 2015; Santin et al, 2016; Van Allen et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…POLE ‐mutant colorectal and endometrial cancers have an excellent prognosis 8, 11, 12, 13, probably owing to a robust antitumour immune response against the multitude of immunogenic neoantigens that they are predicted to harbour 11, 14, 15. Very recent reports have also suggested that these tumours may be highly responsive to immune checkpoint inhibition 16.…”
Section: Introductionmentioning
confidence: 99%